Lifestyle and the hypertensive disorders of pregnancy in nulliparous women in the United States: a secondary data analysis of the nuMom2b - Elizabeth Mollard; Constance Cottrell (BMC, 2023)
Abstract Background Hypertensive disorders of pregnancy are a leading cause of maternal and fetal morbidity and mortality and a significant risk factor for future cardiovascular disease development in women. This study aimed to explore lifestyle wellness-related variables and how they impact the risk of hypertension in pregnancy. Methods This is a secondary analysis of data from the prospective cohort study Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-To-Be (nuMoM2b). Data was collected through questionnaires, clinical evaluations, and medical records review at 8 academic medical centers in the United States. Four study visits were scheduled throughout the participant's pregnancy (visits one-four): 60-136, 160-216, and 220-296 weeks gestation and birth. A series of statistical modeling and logistical regression were performed using 15 lifestyle variables related to sleep, nutrition, resilience, illness avoidance, and physical activity were selected as predictor variables with an outcome variable of hypertension. Results Of 9289 nulliparous participants considered for inclusion in our analyses, 1464 had any HDP during study participation, and 554 participants had complete data available for the study and were included in our final sample. Results were statistically significant at a level of p < 0.05. Of the sleep variables, snoring at visit 1 increased the risk of hypertension in pregnancy. Greater vegetable consumption reported at visit one decreased risks of hypertension in pregnancy. Physical activity reported at visit two and visit three were associated with decreased risk of hypertension. Physical activity reported at visit three combined with more hours of sleep each night, or through napping habit reported at visit one decreased hypertension risk. Increased fish oil consumption combined with more hours of sleep at visit one increased odds of hypertension in pregnancy. Conclusions Our results support that lifestyle wellness-related variables relating to sleep, physical activity and nutrition affect hypertension in pregnancy. The studied variables and others should be considered in future research and intervention development to reduce hypertension in pregnancy and improve maternal wellness.